Product liability: Detecting potential risks in new product - Andrea Castellano; Gustavo Ferro; Maximiliano Miranda Zanetti (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2023)
The central hypothesis of this article is that liability regulation can foster firms' incentives to study the (potential) dangers of their products. We discuss alternative views and develop a formal model to analyze a firm's incentive structure under the application of hindsight liability. We find a new role for liability regulation: to foster voluntary investment in research aimed at detecting potential risks in new products. The model allows us to analyze the firm's investment decisions in research under different scenarios, each of which has varying expected costs. We offer some alternatives for institutional design seeking incentive compatibility with the aim proposed.
Keywords: K12; K22; 330; risk; regulation; product liability; incentives; asymmetric information